PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT MENABUNG NASABAH BANK ACEH - Aulia Fitri; Ainal Firza (Indonesian Journal of Islamic and Social Science, 2023)
Attractive and promising promotions can attract customers' interest in using a product. Apart from promotions, there is another thing that really influences customers' interest in saving, namely service quality, because good service can make customers comfortable and feel safe in using the bank's products. So the author is interested in conducting further research on the influence and quality of service on interest. The purpose of this research is to find out how much influence promotions and service quality influence customers' interest in saving at Bank Aceh Syariah Bireuen Branch. The type of research used is quantitative research. The hypotheses in this research are promotion, service quality, and customer interest in saving. Based on the results of research carried out through the data collection stage by distributing questionnaires to 52 customers with various statements and questions and tested using the SPSS version 25 application. It can be concluded that in the t test coefficient table (partial) it can be seen that the calculated t value of the promotion variable is 2.258 > 2.009, and the significance value is 0.026 < 0.05. then a decision can be taken that the promotion variable (X1) has a positive effect on customers' interest in saving.